Production Of Biodiesel From Jatropha Curcas L. Oil Catalyzed By SO42-/ZrO2 - Yee , Kian Fei (2010)
Biodiesel which is derived from non-edible oil such as Jatropha curcas L. oil has a better potential compare to edible oil to replace petroleum-derived diesel fuel as it does not compete with food resources. However, Jatropha curcas L. oil contains high free fatty acids, which is far beyond the limit that can be tolerated by homogeneous alkaline catalyst. Therefore, heterogeneous acid catalyst is required to eliminate soap formation in the product mixture. In this study, two simplified methods to prepare sulfated zirconia loaded on alumina (SZA) catalyst for transesterification of Jatropha curcas L. oil with methanol to biodiesel is reported. The catalysts were prepared by direct sulfation of zirconia oxide method and solvent- free method. The catalysts were characterized by X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), pyridine- FTIR and BET surface area measurement.